Young adult sexual offenders with emerging personality disorders: developmental and offence-related characteristics and treatment engagement. Issue 2 (4th May 2019) - Eastman, Oliver; Craissati, Jackie; Shaw, Jake
ABSTRACT: In the context of the UK Government's Offender Personality Disorder (OPD) Strategy, large numbers of high-risk young adult sexual offenders with emerging personality disorders are being screened for inclusion onto specialist intervention pathways (the OPD Pathway). However, little is currently known about the clinical and offence-related needs of this population or their impact on treatment engagement. The current study investigated the developmental, personality and offence-related characteristics of 87 incarcerated young adult sexual offenders, comparing those screened in to the pathway and those not screened in. Fifty per cent of the sample were potentially eligible for the OPD pathway. OPD eligible cases were found to have significantly higher rates of parental difficulties, developmental trauma, and childhood behavioural difficulties and to present with significantly higher rates of previous violent and sexual offences, previous allegations of sexual offences, and to have used physical coercion in their offences. The OPD sample was also significantly less likely to have pre-pubescent victims and more likely to refuse treatment, with over 70% failing to engage with the Sex Offender Treatment Programme (SOTP). SOTP non-engagement among OPD cases was most strongly predicted by categorical offence denial. Comparisons are made with the broader adolescent sexual offender literature.